A rare case of pulmonary endobronchial spindle cell carcinoma with liver metastasis along with concurrent cutaneous neurofibroma - Pratap Upadhya; C. Sivaselvi; Christie George Joseph; Bheemanathi Hanuman Srinivas (The Journal of Association of Chest Physicians)
Spindle cell carcinoma is one of the histological variants of pulmonary sarcomatoid carcinoma. It is a rare, poorly differentiated, highly malignant, and rapidly growing non-small cell carcinoma of the lung. Information about pulmonary spindle carcinoma incidence, clinical features, and immunohistochemical markers are not well known compared to other variants of sarcomatoid carcinoma. Most sarcomatoid carcinoma features mimic non-small cell carcinoma, so it is easily misdiagnosed. Cutaneous neurofibroma with primary lung spindle cell carcinoma has not been reported in any previous literature. Here we report a rare endobronchial sarcoma with liver metastasis and concurrent skin neurofibroma.